The contribution of forest coffee certification program to household income and resource conservation: Empirical evidences from Southwest Ethiopia - Diriba Abdeta; Alemayehu N. Ayana (Environmental and Sustainability Indicators)
Coffee certification programs are emerging as potential tools to improve livelihoods and contribute to environmental sustainability. However, these programs have faced criticism, particularly regarding their impact on participants' livelihoods and resource conservation. This study evaluates the performance of the Forest Coffee Certification Program (FCCP), implemented in the Belete-Gera forest area over the past ten years (2011–2022), focusing on its contributions to household income and its effects on resource conservation. Additionally, it investigates whether premium payments resulting from the certification have incentivized households to comply with FCCP objectives and requirements. Multiple data collection methods were employed, including household surveys, key informant interviews, stakeholder workshops, and desk reviews. Results indicate a substantial increase in the total sales volume of forest coffee and revenues, whereas the volumes of forest coffee supplied to the cooperatives showed decreasing trends over the past ten years. Consequently, the premium payment received from certified forest coffee export also showed a substantial decreasing trend. The current premium payment of $0.87 (46 birr) per kg is identified as the optimal incentive for compliance with FCCP requirements. The results also indicate that the certification program contributed to forest conservation by creating incentives that fostered a sense of ownership within the local community, particularly during the early stages of its implementation. The study concludes that improving price differentials and ensuring fairer premium distribution could strengthen the FCCP's impact on livelihoods and forest conservation. Moreover, the program needs to address the decreasing trend in forest coffee cooperative supplies to sustain its long-term benefits.